Detection of aqueous alteration minerals in Martian open and closed paleolake basins. (15th November 2021) - Alemanno, G.; Orofino, V.; Maturilli, A.; Helbert, J.; Mancarella, F.
Abstract: Candidate closed- and open-basin lakes have been widely observed on the Martian surface. Many of them show the presence of exposed sediments of possible lacustrine origin. Understanding the mineralogy of these structures provide insights on the nature of processes that originated and shaped their interior and on the role of liquid water on Mars. Spectral data obtained from the Compact Reconnaissance Imaging Spectrometer for Mars (CRISM) have been so far analyzed with particular attention to the possible detection of aqueous alteration minerals. In this work, we mapped 16 closed-basins and 39 open-basins, not present in the past published Martian basins maps. We looked for recent CRISM observations of these and other previously mapped open- and closed-basin lakes. We further confirmed the presence of water alteration minerals in two previously analyzed structures and discovered other deposits of such minerals in two of the newly mapped sites. Light-toned bedrock exposures that show the presence of hydrated minerals (such as Fe/Mg smectites) along with unaltered mafic material (olivine) have been observed. Based on our observations and the comparison with the literature, it can be deduced that the observed deposits are most probably of lacustrine origin. Furthermore, the location of these deposits of altered minerals suggests that, at least in one case (where altered material has been detected on the floor of the outlet valley), the observed minerals have likely been transported within the lacustrine deposits rather than altered in situ . To the best of our knowledge, this is the first time that this occurrence has been observed and it is an indication of presence of such kind of minerals even in small valleys. Highlights: CRISM observations on new and previously mapped open- and closed-basin lakes have been here investigated. Our study revealed the presence of water alteration minerals in four of the analyzed structures. The location of the detected minerals suggests that, at least in one case, those are likely transported lacustrine deposits.